Technoscience, corpus, gender and sexuality - Manica, Daniela Tonelli (2015)
Our focus, in this dossier, is to try to resume an effort of reflection on the terms announced in the call (technoscience, bodies, gender and sexuality) focusing specifically on the dialogue between the social studies of science (and, particularly, with a socio-anthropology of science and technology) and gender studies. We propose to think about them in relation to the analyzes that both fields make about the production of knowledge and techno-scientific interventions on sexed/gendered bodies.